Major and trace element zoning in plagioclase from Kizimen Volcano (Kamchatka): Insights into magma-chamber processes - Churikova T.G.; Ivanov B.V.; Eichelberger J.; Wörner G.; Browne B.; Izbekov P. (My University, 2013)
The data on the geochemistry of the rocks of Kizimen Volcano and results of microprobe studies of major and trace elements in plagioclase grains from acid lavas and basalt inclusions are presented. The characteristics of the Kizimen Volcano are the following: (1) basalt inclusions are abundant in acid lavas; (2) banded, mixed lavas occur; (3) the distribution curves of rare earth elements of acidic lavas and basalt inclusions intersect; (4) Sr–Nd isotope systematics of the rocks and inclusions do not indicate mixture with crustal material; (5) plagioclase phenocrysts are of direct and reverse zonation; (6) olivine and hornblende, as well as acid and mafic plagioclases, coexist in the rocks. The studies revealed that the rocks are of a hybrid nature and originated in the course of repeated mixture of acid and mafic melts either with chemical and ther mal interaction of melts or exclusively thermal ones. Study of the major and trace element distribution in zonal minerals provides an informative tool for understanding the history of the generation and evolution of melts in a magma chamber
Keywords: 38.37.19 Магматизм и магматические горные породы; 38.37.25 Вулканология; Кизимен; Kamchatka